Algeria’s Experience in Building a Venture Capital Sector - messaoudi, moaad (Journal of Research in Finance and Accounting, 2023)
This study aims to define venture capital as a concept and a new alternative in the fild of finance and investment and its applicability in Algeria, as well as review Algeria’s experience in building a venture capital sector. The results show that, institutional frameworks play an important role to attract venture capital funding and organize venture capital ecosystem.